Important Strategies for Preventing Hypertension Through Risk Factor Approaches - Nasution, Ali Napiah; Ginting, Chrismis Novalinda; Siregar, Reza Arfan (Indonesian Journal of Global Health Research, 2024)
Hypertension causes high morbidity (sickness) and mortality (death). Hypertension occurs as a result of interactions and various risk factors that a person has. Multiple studies have linked various risk factors to the emergence of hypertension. The research aims to determine the Essential Hypertension strategy through a risk factor approach at the Asy-Asyifa Clinic. The research design used was an analytical study with a case-control study design by selecting cases who suffered from essential hypertension and controls who did not suffer from essential hypertension. Primary data collection was carried out directly by researchers using research instruments in the form of questionnaires. In fact, the results of this study determined that age is related to the incidence of hypertension. The higher the age group, the more often the incidence of hypertension. The results of the Chi-Square statistical test with a value of p = 0.06 mean that there is a significant relationship between obesity and the incidence of hypertension. The results of the Chi-Square statistical test with a value of p = 0.048 mean that there is an essential relationship between people who smoke and the incidence of hypertension. In this study, there was no significant relationship with the Chi-Square statistical test with a value of p = 0.020, meaning that there was a meaningful relationship between people who consumed much salt and the incidence of hypertension. The variables influencing essential hypertension are obesity, salt consumption, and age. The dominant variable that influences essential hypertension at the Asy-Asyifa Clinic in Medan is the obesity variable. Regular exercise and a balanced diet are crucial to maintaining a healthy weight.